You are on page 1of 5

Transposing (Re-arranging) Equations

Andrew Roberts
4th March 2004

Re-arranging equations is an essential skill in maths (and any applied maths subject
for that matter). Fortunately, it is fairly straightforward — it merely relies on a simple
principle, and a small set of rules. Once learned, it is a rather mechanical process to
get an equation in one form, into another. Finally, I can not stress enough that like any
mathematical skill, it also requires a decent amount of practise!

Principle of balance
I dare say that in maths textbooks, they will not refer to this principle, as I have
just made it up myself! However, this is the way I prefer to think about transposing
equations, and I think it helps make the process a lot easier (well, I would say that,
wouldn’t I?!)

Figure 1: A set of scales.

Figure 1 shows a set of scales. As you will no doubt understand, if the scales are level
(that is, balanced) then the weight on the left-hand side (LHS) must be equal to the
weight on the right-hand side (RHS). Of course, it does not matter how those weights
are composed. So, you could have a kilo of sugar on one side and a kilo of flour on the
other, and the scales would balance. Alternatively, you could have a kilogram weight on
one side, and four 250g weights on the other. These two weights are equivalent, and
therefore the scales would balance.
So how does the scales analogy relate to equations? Well, an equation is composed
of two sides also. There is an expression on the LHS, and another on the RHS. They
are separated with an equals sign (=), which indicates that they are equal — or that
the equation is balanced. If you wish to alter the LHS expression, then you must also do
the exact same thing to the RHS to ensure that the equation remains balanced. Going
back to the balanced scales, and add 500g to the LHS, it is clearly now heavier on that

side. To regain the equilibrium, all you need to do is add 500g to the RHS, and the
scales will be balanced again.
Therefore, to summarise, the principle of balance is basically this: whatever you do
to one side of the equation, do the same to the other side!

An example
So far, all this guide has done was rambled on about balance! As important as I believe
that is, it is about time to get stuck in with a meaty example, from which I hope to
extract a set of rules. Here is our example:
µ ¶2
x= 10 − −z
The goal is to re-arrange the equation to make it equal to y.
The first aim is to isolate the sub-expression that contains our target variable, y,
which is − 4y
g . To do this, you must approach from the outside, working inwards. The
You can see that the entire RHS expression is wrapped up in parentheses and is
squared. We must therefore remove this from the RHS. This is done by taking the
square-root (of both sides). This leaves us with:
√ 4y
x = 10 − −z
Our target sub-expression now has two constants either-side. It has 10 to its left,
and −z to its right. 10 is a positive number, and so to remove it from the RHS, we
must subtract 10 from both sides. Similarly, with −z, to remove it from the RHS, we
must add z to both sides.

√ 4y
⇒ x − 10 + z = (10 − 10) − + (−z + z)
√ 4y
⇒ x − 10 + z = 0− +0
√ 4y
⇒ x − 10 + z = −
Ok, so, we are now left with our sub-expression, which now means we can focus on
just isolating the y. Next, although not entirely necessary, I would normally prefer to
eliminate the negative in front of our target sub-expression. This is simply a matter of
multiplying both sides by −1.

¡√ ¢ 4y
⇒ − x − 10 + z =
√ 4y
⇒ − x + 10 − z =
√ 4y
⇒ 10 − x−z =
Our y is currently trapped because it is part of a fraction. Our target is part of the
numerator, and so we need to remove the denominator, which in this instance simply
consists of g. To remove denominators, all you do is multiply both sides by whatever
the denominator is. Therefore, for this example, we need to multiply both sides by g.

¡ √ ¢ 4y
⇒ g 10 − x − z = g
¡ √ ¢ 4yg
⇒ g 10 − x − z =
¡ √ ¢ 4y g¢
⇒ g 10 − x − z =

¡ √ ¢
⇒ g 10 − x − z = 4y

Only one step left before we reach our goal. As you can see, y is still being multiplied
by 4. We just want y, and so to get rid of the 4 from the RHS, simply divide both sides
by 4. This is because any number divided by itself always gives 1.

g (10 − x − z) 4y
⇒ =
4 4

g (10 − x − z)
= ¢4y
√ 4¢
g (10 − x − z)
⇒ = y
The end! We now have managed to re-arrange the original equation so that it is
equal to y.

Another quick example

What would have happened if our target variable was part of a fraction, but this time it
was within the denominator? For example, re-arrange the following so that it is equal
to y:
We can not remove the numerator in a single step. We first remove y from the
denominator by multiplying both sides by y.

⇒ xy =
100g y¢
⇒ xy =

⇒ xy = 100g

The result of this was to move cancel out y from the RHS, and move it over the the
LHS. Now, the remaining step is to uncouple xy so that we are just left with y. This
is done by dividing both sides by x.

xy 100g
⇒ =
x x
xy 100g
⇒ =
x x
⇒ y =

Rules of re-arranging
Hopefully, from working through a couple of examples, you should begin to see a pattern
about how to approach each step. Whilst isolating your target variable, you need to
look at how the other sub-expressions are attached, you then do the opposite! So, if
there is an expression attached to your target expression by addition, then you subtract
from both sides. If there is an expression attached by multiplication, then you divide
both sides, etc. Here is a summary of the basic rules:

Start End Why it works

x=y+z y =x−z Because z − z = 0
x=y−z y =z−x Because −z + z = 0
x = yz y = xz Because zz = 1
x = yz y = xz Because z · z1 = 1
x = yz y = xz Because I just showed it above!
√ √
x = yz y= zx Because¡ z y z¢ = y
√ √ z
x= zy y = xz Because z y = y

Table 1: Summary of rules.

You will recall from the introduction, that it is all very well seeing this stuff in action,
but until you actually try it yourself and gain the necessary experience, you will not
actually possess this skill. So, here are some exercises to get the required practise.
Solutions are included afterwards, so you can check that you are doing things correctly.

1. Re-arrange the following equations to make them equal to y:

(a) x = yz + 5
(b) x = zy 2

(c) 10x = 2 y
(d) x = yv

2. Re-arrange the following equations in order to find all possible unknowns:

(a) E = mc2 (re-arrange for m and c.)

1 1 1
(b) f = u + v
(c) X = L3

(a) y = z
(b) y = z
¡ 10x ¢2 2
(c) y = 2 = (5x) = 25x2
(d) y = vx


(a) m = cE2
c= m
= u1 + v1
¡ ¢−1
(b) f = 1 1
³ ´−1
1 1
u= f − v
³ ´−1
1 1
v= f − u
3 mu2
(c) L = x
u= m
L3 X
m= u2